Auditing Advanced EDP Systems: A Survey of Practice and Development of a Theory (Book). - Meyer, Philip E.; Messier, William F. (The Accounting Review, 1984)
Reviews the book "Auditing Advanced EDP Systems: A Survey of Practice and Development of a Theory," by Gordon B. Davis and Ron Weber.